Who are an organization's stakeholders and to what extent should an organization have regard to their interests? - Kaler, John (Henry Stewart Talks, 2011)
Fundamentals of the stakeholder approach, Influencer and Claimant definitions, Opposing criteria for stakeholder identification, Opposing conceptions of organizational purpose, Stakeholders recognized under each definition, Extent to which stakeholder interests should be served under each definition, The definitions in practice (with reference to section 172 of the Companies Act 2006)